Deferential Tailoring: a grounded theory of how women respond and adapt to social conditions and gender-related challenges in the New Zealand construction industry. Issue 2 (1st February 2023) - Hegarty, Terrelle; Wright, Sarah; Wordsworth, Russell; Lord, Beverley
Abstract: In this article we utilize grounded theory to explore women's experiences in the unique construction industry context that followed the 2010 Canterbury (New Zealand) earthquakes. Data were obtained from 36 semi-structured interviews conducted with women working in a variety of occupations in the construction industry. We identify three inter-related categories: capitalizing on opportunity, demonstrating capability and surface tolerance, which together represent a response process that we label "deferential tailoring". The deferential tailoring process explains how women intentionally shape their response to industry conditions through self-regulating behaviours that enables them to successfully seize opportunities and manage gender-related challenges in the working environment. Our findings challenge existing research which suggests that women adopt submissive coping strategies to conform to androcentric norms in the construction industry. Instead, we argue that the process of deferential tailoring can empower women to build positive workplace relationships, enhance career development, and help shift perceptions of the value of their work in the industry.